Perlindungan Hukum Terhadap Kebebasan Pers (Wartawan) Dalam Melakukan Kegiatan Jurnalistik - Nikodemus, Jimris Fantos; Latupeirissa, Julianus Edwin; Ubwarin, Erwin (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Freedom of the press is fundamental. Freedom is meant in the context of exercising the rights, functions and roles of the press. Journalists as people who carry out these functions and roles, get guaranteed legal protection. In Article 8 of Law No. 40 of 1999 concerning the Press it states